Middle East Survey : The Political, Social and Religious Problems - Morrison, S. A. (London SCM Press Ltd., 1954)
A general survey of the Middle East with information on its geography, languages, religions, history, occupations, family life, cities, education, food, and legacies.
Include Bibliography and Index.
The Political, Social, and Religious Problems.
Keywords: Middle East -- Survey, Middle East